2021
DOI: 10.1177/21650799211038499
|View full text |Cite
|
Sign up to set email alerts
|

“We All Held Our Own”: Job Demands and Resources at Individual, Leader, Group, and Organizational Levels During COVID-19 Outbreak in Health Care. A Multi-Source Qualitative Study

Abstract: Background: Interventions tackling COVID-19 impact on health care workers’ mental health would benefit from being informed by validated and integrated assessment frameworks. This study aimed to explore the fitness of integrating the Job Demands-Resources (JD-R) model and the Individual-Group-Leader-Organization (IGLO) framework to investigate the pandemic’s impact on health care workers’ mental health. Methods: Qualitative data were collected via 21 semi-structured interviews with senior and middle managers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(57 citation statements)
references
References 33 publications
(40 reference statements)
5
16
1
Order By: Relevance
“…We can identify the proactivity behavior toward safety and health at work as a form of engagement with the organization that in turn may limit the risk of exhaustion, especially in times of crisis and uncertainties that, on the contrary, may expose to a greater risk of stress and burnout. This is in accordance with recent qualitative studies conducted in the healthcare sector [ 34 ] that reported how proactivity, motivation, and personal initiatives were recognized as personal resources functional to sustain a better adaptation in the difficult times of the COVID-19 pandemic. However, future studies can evaluate more complex relationships between safety participation behaviors and stress reactions.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We can identify the proactivity behavior toward safety and health at work as a form of engagement with the organization that in turn may limit the risk of exhaustion, especially in times of crisis and uncertainties that, on the contrary, may expose to a greater risk of stress and burnout. This is in accordance with recent qualitative studies conducted in the healthcare sector [ 34 ] that reported how proactivity, motivation, and personal initiatives were recognized as personal resources functional to sustain a better adaptation in the difficult times of the COVID-19 pandemic. However, future studies can evaluate more complex relationships between safety participation behaviors and stress reactions.…”
Section: Discussionsupporting
confidence: 91%
“…On the other side, quantitative job demand overload emerged as a significant job demand in the relationship with emotional exhaustion for both WPs and WBs. Consistent with existing evidence from different occupations [ 31 , 33 , 34 , 35 ], we can confirm that employees of the public administrative sector that continued, or suddenly returned to work, since the first phases of the pandemic had to significantly bear an increase in job-related demands. This has probably been affected by new work procedures and schedules, as well as the need to manage work with remote colleagues and at the same time having to maintain and comply with the procedures for the prevention of contagion that involved work organization of both WPs and WBs.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Given predicted shortages of nurses in the future [ 8 ] and Generation Y nurses’ (i.e., born between 1980 and 1994) strong desire for work–life balance [ 43 ], any action that can balance the needs for service delivery with the needs of staff is highly recommended. Giusino et al’s findings [ 44 ] suggests that HCP’s mental health should be addressed on multiple levels (individual, the group, the leader, and the organization) as COVID-19 related job demands and resources are found at all levels [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a health and safety culture is needed, especially mental health interventions at the individual, group, and organizational level among healthcare workers. The interventions need to address the impact of COVID-19 on the mental health of healthcare workers by identifying the job demands and resources and understanding the barriers to achieving effective outcomes in terms of health and well-being within their work environment [51].…”
Section: Discussionmentioning
confidence: 99%